1983
DOI: 10.1172/jci110860
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of antibodies to hepatitis B virus by cultured lymphocytes from chronic hepatitis B surface antigen carriers.

Abstract: A B S T R A C T It hasIn order to identify the mechanisms for the lack of detectable anti-HBs synthesis by chronic HBsAg carrier lymphocytes, co-culture experiments were performed using T and B lymphocyte fractions that had been purified by affinity chromatography. B lymphocytes from carriers co-cultured with allogeneic irradiated ("helper") T lymphocytes from controls synthesized normal amounts of IgG, IgM, and anti-HBc Dr. Dusheiko was the recipient of a South African Research Council Overseas Scholarship. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 28 publications
2
44
1
Order By: Relevance
“…Cocultures of B cells derived from vaccine recipients together with autologous or allogeneic HLA-class II-matched ormismatched T cell preparations resulted in a strong increase of HBs-specific SFC. Thus, it could be confirmed that anti-HBs antibody formation is dependent on the presence of T cells but not restricted to identical HLA molecules [12,13,25,30]. It can be speculated that this T cell help is mediated by alloreactive T cell stimulation followed by the release of cytokines or the expression of adhesion molecules.…”
Section: Regulation Of Anti-hbs Immune Response In Vitro 55mentioning
confidence: 93%
See 2 more Smart Citations
“…Cocultures of B cells derived from vaccine recipients together with autologous or allogeneic HLA-class II-matched ormismatched T cell preparations resulted in a strong increase of HBs-specific SFC. Thus, it could be confirmed that anti-HBs antibody formation is dependent on the presence of T cells but not restricted to identical HLA molecules [12,13,25,30]. It can be speculated that this T cell help is mediated by alloreactive T cell stimulation followed by the release of cytokines or the expression of adhesion molecules.…”
Section: Regulation Of Anti-hbs Immune Response In Vitro 55mentioning
confidence: 93%
“…In addition, an association of the HLA class II allele DRB1*1302 with protection against persistent HBV infection was shown [11]. Recent studies have suggested defective T and B cell functions [12,13]. A general problem of these studies was the low sensitivity of the in vitro assays used to detect HBs-specific antibody production [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accordance with previous reports of a defect in anti-HBs antibody production of PBMC derived from chronic HBV patients. 29 In apparent contradiction to these data, a recent study described the existence of antienvelope antibodies in immune complexes in sera of the majority of CHB patients by the use of more sensitive assays. 8 However, these antibodies have nei- ther been compared with the titers of individuals who had recovered from HBV infection or been characterized in terms of epitope specificity (i.e., preS or HBs).…”
Section: Discussionmentioning
confidence: 97%
“…29 However, in more recent studies, the existence of antienvelope antibodies in immune complexes was shown in sera of patients with CHB, arguing for a merely quantitative defect in anti-HBs antibody secretion. 8 Using a novel chimeric mouse model, our report shows the dependence of the human anti-HBs response on the activation of HBs-specific Th1 cells.…”
Section: Discussionmentioning
confidence: 99%